Man Vs Machine: Battle of Wits in Writing - Sarifah Achmad; Angelina Pasha Rami Pratiwi (Indonesia Technology-Enhanced Language Learning (iTELL) Journal, 2024)
This study intended to compare the short stories written by students and those generated by AI. The use of AI in the current educational context seems inevitable without opposition in the creative writing field. Administering creative writing scoring rubrics, a comparative study employing analysis was carried out. The four aspects of short story writing: 1) Image, 2) Voice, 3) Characterization, and 4) Narrative, were examined. The scoring rubric aspects were instigated as the comparison value. Through the study, the following results were described: 1) There were similar and different qualities performed by students written short stories and AI-generated short stories, 2) There were dominances and lowliness aspects performed by students written short stories and AI-generated short stories, 3) The dominance of students written short stories were pertained to the characterization and voice, while the AI-generated short stories were dominant in Image application. For the narrative aspects of the short stories, it was found a tie. This study implied that language learners to use AI carefully particularly in the field of creative writing.